Social media usage and cultural identity of Chinese students in Malaysia - Zhao, Wenwen; Osman, Mohd Nizam; Omar, Siti Zobidah; Yaakup, Hani Salwah (Human Resource Management Academic Research Society, 2023)
Social media has become increasingly important for international students and influence their cultural identity. However, there is limited research on the relationship between social media and cultural identity. This study conducted an online survey of 438 Chinese students in Malaysia to investigate the relationship between social media usage motivations (information, social, entertainment, and acculturation) and cultural identity (Malaysian and Chinese cultural identity). The data was analyzed using SPSS and AMOS. The results demonstrated that different motivations for using social media had varying influences on cultural identity. Regarding Malaysian cultural identity, only entertainment usage was unrelated, while acculturation usage had the strongest correlation. For Chinese cultural identity, entertainment and acculturation usage were unrelated, while information and social usage showed a positive correlation.